The Moderation Role of Tax Rate Reduction and Firm Size on the Effects of Tax Aggressiveness on Company Value - Faisal Ardhi; Arief Wibisono Lubis (Yayasan Ilomata, 2023)
This study aims to examine the impacts of reducing tax rates and firm size on tax aggressiveness in regards to the company value in Indonesia. This study used 302 samples of companies with 1,118 observation points within the period of 2017 - 2021. The proxy measurement of tax aggressiveness is with Effective Tax Rate and the company value using Tobins'Q. The research analysis was carried out using multiple regression models of panel data employing fixed effects as the best research model. The results showed that there was no significant effect of aggressive tax on firm value. This study also found that a decrease in tax rates did not affect the relationship between tax aggressiveness and firm value, but firm size did impact on both tax aggressiveness and firm value.